2014
DOI: 10.1038/cddis.2014.452
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of POU4F2/Brn-3b with p53 may be important for controlling expression of pro-apoptotic genes in cardiomyocytes following ischaemic/hypoxic insults

Abstract: Cardiomyocyte death following ischaemic/hypoxic injury causes irreversible damage to cardiac function and contributes to chronic diseases such as heart failure. Understanding the mechanisms associated with myocyte loss under these conditions can help to identify strategies to minimise/abrogate such detrimental effects. The p53 protein can induce apoptosis or cell cycle arrest, but effects on cell fate depend on interactions with other regulators such as POU4F2/Brn-3b (Brn-3b), which co-operates with p53 to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 60 publications
3
40
0
1
Order By: Relevance
“…Cells subjected to OGD exhibited only very low levels of apoptosis, as measured by TUNEL or AxV staining, and these very low levels were unaffected by HDL treatment ( Figure 1B–D ). The lack of cardiomyocyte apoptosis following 4 h of OGD in our experiment is consistent with a recent report that 4 h of OGD induced significant cell death with little detectable apoptosis in neonatal rat ventricular cardiomyocytes [ 24 ]. Despite the low levels of apoptosis, exposure of HIVCM to 4 h of OGD caused membrane permeabilization (a marker of necrotic or necroptotic cell death) as evidenced by increased nuclear staining with PI compared with corresponding normoxic controls (82.6 ± 1.7 vs. 0 ± 0% PI-positive cardiomyocytes, Figure 1E,G ), and treatment with HDL attenuated PI uptake (49.2 ± 12.1 vs. 82.6 ± 1.7% PI-positive cardiomyocytes, Figure 1E,G ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Cells subjected to OGD exhibited only very low levels of apoptosis, as measured by TUNEL or AxV staining, and these very low levels were unaffected by HDL treatment ( Figure 1B–D ). The lack of cardiomyocyte apoptosis following 4 h of OGD in our experiment is consistent with a recent report that 4 h of OGD induced significant cell death with little detectable apoptosis in neonatal rat ventricular cardiomyocytes [ 24 ]. Despite the low levels of apoptosis, exposure of HIVCM to 4 h of OGD caused membrane permeabilization (a marker of necrotic or necroptotic cell death) as evidenced by increased nuclear staining with PI compared with corresponding normoxic controls (82.6 ± 1.7 vs. 0 ± 0% PI-positive cardiomyocytes, Figure 1E,G ), and treatment with HDL attenuated PI uptake (49.2 ± 12.1 vs. 82.6 ± 1.7% PI-positive cardiomyocytes, Figure 1E,G ).…”
Section: Resultssupporting
confidence: 93%
“…We sought to determine if HDL could protect cardiomyocytes against cell death induced by OGD as a model of induced ischemia and to evaluate if SR-B1, PI3K, and AKT are involved in the protective signaling elicited by HDL. Others have shown that following 4 h of hypoxic stress, neonatal rat ventricular cardiomyocyte cell death was a result of necrosis, though reoxygenating cells for increasing lengths of time resulted in a shift of cell death from necrosis to apoptosis [ 24 ]. Similarly, we found that in HIVCM and NMCM exposed to OGD for 4 h, necrosis (detected by PI staining) was the primary driver of cell death, and that there was little to no induction of apoptosis (as evidenced by a lack of TUNEL or AxV staining), or necroptosis (as evidenced by resistance to the necroptosis inhibitor, Nec-1s).…”
Section: Discussionmentioning
confidence: 99%
“…В развитии гормонозависимых опухолей чело-века большое значение имеют транскрипционные факторы POU4F1, также известные как нейроген-ные факторы Brn-3α [1]. Они представляют собой важные ядерные белки, регулирующие процессы пролиферации и дифференцировки клетки.…”
unclassified
“…Cardiomyocytes death occurs following coronary artery occlusion can cause irreversible damage to the heart because these terminally differentiated cells have poor regenerative capacity and are not readily replaced (Budhram-Mahadeo et al 2014). It is important to understand the mechanisms associated with cardiomyocyte loss under these conditions.…”
Section: Discussionmentioning
confidence: 99%